2001
DOI: 10.1007/s002680020378
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal Treatment of Internal Carotid Artery Stenosis

Abstract: Percutaneous transluminal stent-angioplasty of the carotid artery has indications that are similar but not identical to those for carotid surgery. Certain clinical conditions and morphologic findings, such as myocardial infarction, occlusion of the contralateral carotid artery, or tandem stenoses, favor use of the endoluminal technique. On the other hand, large clots at the site of stenosis, heavily calcified plaques, or elongated, kinked carotid arteries are better suited for carotid endarterectomy. Our exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 12 publications
0
26
0
1
Order By: Relevance
“…For the moment, only a few series of cases with long-term follow-up after CAS have been reported, [6][7][8][9]30 and no studies have analyzed the behavior of the implanted stent over time on the basis of the different stent materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the moment, only a few series of cases with long-term follow-up after CAS have been reported, [6][7][8][9]30 and no studies have analyzed the behavior of the implanted stent over time on the basis of the different stent materials.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these trials did neglect to publish longterm results after CAS, and only a few nonrandomized studies have focused their attention on long-term results with Ͼ5 years of follow-up. [5][6][7][8][9] As demonstrated by several RCTs comparing the efficacy of CEA vs medical therapy, even after successful carotid revascularization late ipsilateral stroke occurs in 5.1-13% at 5 years. [10][11][12][13][14] The major concern for long-term results after CAS is, therefore, that the plaque, which is completely removed in CEA surgery, is only remodeled and contained behind the strut of the stent, so that the only protection against late embolization is the scaffolding of the emboligenic plaque by means of the stent.…”
mentioning
confidence: 99%
“…16,18 Carotid artery angioplasty was introduced in 1979, 19 and the first carotid stent in 1989. 20 As newer techniques in endovascular therapy evolve, such as the use of distal cerebral protection devices, and with more experience, CAS has been proposed as an alternative to CEA, 2,3,21 particularly in patients at high surgical risk. The data from the Stenting and Angioplasty with Protection in Patients at High Risk for Endarterectomy (SAPPHIRE) trial 2 and the ACCULINK for Revascularization of Carotids in High-Risk Patients (ARCHeR) trial 3 demonstrated clinical outcomes that were not inferior to those reported for CEA in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…It took several years to disseminate this technique into broader clinical application. Registry data showed the feasibility and safety of CAS [23,32,36,42]. After these "proof of the principle" studies, CAS became an evolving technology, at first in special high-risk cases for CEA, such as restenotic lesions after CEA, radiogenic stenoses, very long lesions or difficult anatomic locations for CEA.…”
Section: Introductionmentioning
confidence: 99%